Educação a distância em Santarém: o que revela a avaliação dos cursos de pedagogia - Abreu, Cleise Fonseca de (2012)
The expansion of higher education is a phenomenon that has occurred most sharply from the year 1940 with the reorganization of the countries in the postwar period. In Brazil, the Federal Constitution of 1988 and the interference of international organizations, begins to design a control legislation, certification and assessment of Higher Education. In 1996, with the enactment of the Guidelines and National Education, Distance Education - EAD gain status by type of schooling and has been growing by leaps and bounds, producing a series of legal acts to ensure its quality. The present study aims to analyze the situation of Higher Education Institutions offering the Bachelor in Education in Distance mode, in Santarem, a city located in western Pará state, with a view to assessing the MEC to authorize conducts courses this modality. This is a historical research because they want to understand the dynamics of expansion of higher education since the 1930s, with emphasis on the period from 1990 to 2010, and documentary, as it has the legal acts related to higher education in relation to Recognition of Higher Education Institution to work with EAD, Evaluation and Authorisation of course that the National Evaluation System - promotes SINAES. Presents a qualitative-descriptive approach when, from the Terms of Sanitation Deficiency - TSD, analyzes the situation in which these HEIs were at the time of its accreditation and authorization to work EAD. The research showed that although the official documents use the term generously quality assessment that the MEC has failed to authorize the start of course without the minimum conditions (concept 3) supply, as demonstrated by the Terms of Sanitation produced. The EAD practiced in the region has led to the achievement of diplomas, but urgently needs a serious evaluation of the MEC for the much-touted quality is not a dead letter